Compilation of a Practical Guidebook for Worship as a Strengthening of Faith in the Muallaf House Community (Implementation of the ABCD Method in Community Service at the Muallaf House, Tegal Regency) - Zakiyah; Zaki Mubarok; Iik Rifki Alfian Muiz; Ahmad Thoriq Aziz; Abdul Hakim; Usman Habibullah; Ahmad Dafari; Mufliha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A convert is someone who experiences a leap in religious experience, from being a non-Muslim to converting to Islam and becoming a Muslim. This definition of a convert demonstrates that a convert is not someone who has been educated in Islamic religion and spirituality since childhood. Therefore, an increased understanding of Islamic law and worship, particularly reading and writing the Quran, is also necessary. One of the roles of the Tegal Regency Muallaf House (Rumah Muallaf) in meeting these needs is the role of the House of Muallaf (Rumah Muallaf). However, the programs developed by the House of Muallaf have not always been technically smooth. This is due to the congregation's scattered domiciles, the diversity of professions held by the congregation, the inconsistent enthusiasm of the congregation, and the varying levels of understanding of sharia and worship, as well as the diversity of skills in reading the holy book, the Quran. Community service activities carried out by IAT students aim to understand the situation, reconcile with reality, find a compromise to address challenges, and provide solutions to the problems faced by converts. Developing a practical guidebook for worship and improving Quran reading skills for converts in Tegal Regency is a solution desired by converts. Through the implementation of the ABCD method, with its five steps, the management and members of the Rumah Muallaf community have identified sufficient internal assets to be utilized to realize this practical guidebook for worship.